Investigation of polyamidoamine dendrimers induced DNA condensation and enzymatic degradation of these complexes: an atomic force microscopy study - Gharib Abdelhady, Hosam (2004)
Extensive investigations have been made to try and understand the physical properties and structures of condensed DNA phases in vitro during the past decades (Bloomfield, 1991, Marquet and Houssier, 1991, Bloomfield, 1996). The packing pathways of DNA molecules are three dimensional processes, and are not yet fully understood (Yoshikawa et al., 1997). Distinguishing different single DNA molecules at different locales in time in the presence of condensating or dissociating agents is crucial for understanding the mechanisms of packing and unpacking of DNA molecules. The aim of this study is to provide an increased understanding of the some of the pathways of packing and unpacking of DNA. This aim was achieved by monitoring in time and at molecular scale the interaction between the DNA and polyamidoamine dendrimers, as condensating poly cations, and by observing the dissociation of some of these condensates in time when they were exposed to DNase I enzyme, as a dissociating in vivo agent. The main techniques used were atomic force microscopy (AFM) and gel electrophoresis. We believe that the results could be beneficial to the understanding of the in vivo condensation and dissociation process of certain DNA morphologies.